Analisis Penerapan Storytelling sebagai Metode Pembelajaran pada Mata Kuliah Digital Storytelling Mahasiswa Komunikasi IPB 61 - Erinna Aulia Rifay; Amiruddin Saleh; Harvia Atika Zahira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The storytelling method is increasingly relevant for higher education, particularly in communication-oriented study programs within the digital era. This study examines the application of storytelling as a teaching method in the